2014
DOI: 10.1021/jp509383v
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation on PdO(101) during Temperature-Programmed Reaction Spectroscopy: Role of Oxygen Vacancies

Abstract: We investigated the oxidation of CO on PdO(101) using temperature-programmed reaction spectroscopy (TPRS), reflection absorption infrared spectroscopy (RAIRS), and density functional theory (DFT). We find that about 71% of the CO molecules adsorbed in a saturated layer on PdO(101) transform to CO2 during TPRS, with the CO2 desorbing in two main features centered at 330 and 520 K. RAIRS shows that CO molecules initially adsorb in an atop configuration on coordinatively unsaturated (cus) Pd sites of PdO(101) loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 66 publications
6
70
0
Order By: Relevance
“…135 Two main reaction pathways were observed, at 330 and 520 K. Furthermore, IRRA spectra recorded after increasingly higher annealing temperature indicated that the low-temperature pathway involved a reaction between CO(ads) and the pristine PdO(101) surface, resulting in O v . The remaining CO shifted in adsorption site to atop sites on Pd 3-fold in the O v vicinity.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…135 Two main reaction pathways were observed, at 330 and 520 K. Furthermore, IRRA spectra recorded after increasingly higher annealing temperature indicated that the low-temperature pathway involved a reaction between CO(ads) and the pristine PdO(101) surface, resulting in O v . The remaining CO shifted in adsorption site to atop sites on Pd 3-fold in the O v vicinity.…”
mentioning
confidence: 92%
“…130 The kMC model showed, furthermore, that while the CO oxidation barrier is rate limiting for the reaction on the metallic surface, the CO adsorption strength is limiting the reactivity of the surface oxide. However, CO binding could be much stronger if O vacancies are present in the surface oxide, 135 which would increase the reactivity of the oxide. Alternatively, reactions at the boundary between (metastable) CO(ads) islands and the surface oxide 69 could account for the reactivity observed in the PLIF experiment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These prior investiga-67 tions signal a need for further study of the effects of water on CO oxida-68 tion over transition metal oxides, particularly experimental work using 69 oxide surfaces with well-defined structure. 70 We have previously investigated CO adsorption and oxidation as 71 well as water adsorption on a crystalline PdO(101) thin film [19][20][21][22][23]. 72 We find that the oxidation of CO is facile on PdO(101) as more than 73 70% of the CO molecules in a saturated layer are oxidized to CO 2 during 74 temperature programmed reaction spectroscopy (TPRS) via reaction 75 with the oxide surface [21].…”
mentioning
confidence: 99%